2016
DOI: 10.1002/dta.2106
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of Natesto® testosterone gel and its effects on doping markers

Abstract: The laboratory profile of intranasal testosterone gel has not been previously reported from an anti-doping perspective. Because intranasal testosterone gel is newly available as a commercial product, we sought to examine the laboratory parameters following administration of this formulation, with particular attention to anti-doping guidelines. Five healthy and active male subjects were administered testosterone intranasal gel three times daily for four weeks, using a pattern of five consecutive days on, two da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…collection post-administration22 could also influence a negative or positive outcome since the δ 13 C value will normalize to the athlete's baseline level after a washout time, that is either a normalization of the δ 13 C value back to endogenous in the case of T 27 or a reduction in 19-NA concentration such that it is below the measurement capability of the assay.On the other hand, misuse of steroid preparations that have δ 13 C values further into the exogenous range (less than −29‰) remain easy to detect. For instance, administration of the most 13 C-depleted products (−32.7‰) represent the most likely to yield positive results by GC-C-IRMS analysis as demonstrated in previous studies 28. …”
supporting
confidence: 67%
“…collection post-administration22 could also influence a negative or positive outcome since the δ 13 C value will normalize to the athlete's baseline level after a washout time, that is either a normalization of the δ 13 C value back to endogenous in the case of T 27 or a reduction in 19-NA concentration such that it is below the measurement capability of the assay.On the other hand, misuse of steroid preparations that have δ 13 C values further into the exogenous range (less than −29‰) remain easy to detect. For instance, administration of the most 13 C-depleted products (−32.7‰) represent the most likely to yield positive results by GC-C-IRMS analysis as demonstrated in previous studies 28. …”
supporting
confidence: 67%
“…It is possible that longitudinal monitoring of the ABP biomarkers in our participants rather than single urine sampling would have resulted in atypical findings. It has been shown that the implementation of ABP has increased the probability of detecting testosterone gel use in men . It is known that basal T/E ratios are higher in men than in women and that the administration of intramuscular testosterone enanthate affects the T/E ratio to a larger degree in men than in women …”
Section: Discussionmentioning
confidence: 99%
“…The ratios monitored are T/E, A/Etio, 5αAdiol/E, 5αAdiol/5βAdiol, and A/T. It has been shown that the use of ABP increases the sensitivity of detecting the administration of testosterone in men …”
Section: Introductionmentioning
confidence: 99%